2018
DOI: 10.1113/ep086905
|View full text |Cite
|
Sign up to set email alerts
|

Increased skeletal muscle mitochondrial free radical production in peripheral arterial disease despite preserved mitochondrial respiratory capacity

Abstract: Skeletal muscle mitochondrial dysfunction, which is not fully explained by disease-related arterial occlusion, has been implicated in the pathophysiology of peripheral arterial disease (PAD). Therefore, this study comprehensively assessed mitochondrial respiratory function in biopsies from the gastrocnemius of 10 patients with PAD (Fontaine Stage II) and 12 healthy controls (HC). Intramuscular and systemic inflammation, mitochondria-derived reactive oxygen species (ROS) production, and oxidative stress were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“…Similar to the findings on experimental models, PAD patients displayed increased mitochondria-derived ROS production characterized by elevated levels of free radical species [32].…”
Section: Clinical Datasupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to the findings on experimental models, PAD patients displayed increased mitochondria-derived ROS production characterized by elevated levels of free radical species [32].…”
Section: Clinical Datasupporting
confidence: 85%
“…Oxygraphy measurements in PAD patients revealed significantly altered respiratory activity, notably of complexes I, III and IV, and of the acceptor control ratio [27][28][29][30]. Interestingly, more recent studies reported no difference in the mitochondrial respiration rate between PAD patients and healthy controls, despite alterations in O 2 delivery, tissue-reoxygenation and ATP synthesis rate during exercise [31,32]. These conflicting findings could be explained by disparities in disease severity.…”
Section: Clinical Datamentioning
confidence: 99%
“…In support of this, endothelium‐derived NO is thought not only to modulate vascular tone but also to regulate skeletal muscle mitochondrial turnover, suggesting that impairments in NO bioavailability may negatively impact muscle mitochondrial quality and vice versa. Furthermore, increased mitochondrial ROS production and oxidative damage have been recently observed in skeletal muscle from patients with peripheral arterial disease, a vascular disorder often associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…45 PAD was also associated with significant oxidative stress and ROS production. 46 Interestingly, the extend of oxidative damage in PAD gastrocnemius was shown to be associated with advanced disease stage and lower myofibre cross-sectional area. 47 Taken together, these data suggest the pathological implication of excessive oxidative stress in myofibres damage and PAD.…”
Section: B/impaired Muscle Histologymentioning
confidence: 99%